Assesment of pain the critical patient: na experience report (Research, Society and Development, 2022)
Intensive Care Units are environments used for patients at imminent risk of losing their lives, or with organic dysfunction, where their basic needs are affected. Pain is a sensory and emotional experience, being essential for the integrity of the human being, associated with an actual or potential tissue injury, occurring in different intensities. The aim of the study is to report the experience of nursing students in acquiring knowledge about pain assessment in patients admitted to Intensive Care Units. This is an experience report, with a descriptive approach, about experiences in the discipline “Nursing Assistance in the Care of Patients at Risk” from August to December 2021 through synchronous and remote classes. Pain is considered the 5th vital sign, and it is difficult to assess, requiring knowledge and continuing education so that professionals can correctly use and interpret the results of the scales for an effective intervention. This study made it possible to expand knowledge on this topic, better understanding how to proceed to better assess the pain of critically ill patients.